Systematic Literature Review: Green Marketing dan Green Trust - Nisaa, Verselly; Ravelby, Thesa Alif; Permata, Shintya Dwi (Universitas Dharma Andalas, 2025)
The purpose of this systematic literature review (SLR) from 2017 to 2021 is